A CASE OF BULLOUS PEMPHIGOID WITH IMMUNOREACTIVTY TO BLOOD VESSELS AND SWEAT GLANDS - Ana Maria Abreu Velez; Juliana Calle-Isaza; Michael S. Howard (Our Dermatology Online, 2013)
Introduction: Bullous pemphigoid (BP) is one of the most prevalent autoimmune blistering diseases, and believed to be mediated by autoantibodies and complement. The disorder is categorized by the development of urticarial plaques surmounted by subepidermal blisters, and the deposition of immunoglobulins and complement at the basement membrane zone (BMZ) of the skin. Case Report: A 70-year-old male Caucasian patient was evaluated for a four day history of multiple itchy, erythematous blisters on his abdomen. Biopsies for hematoxylin and eosin (H&E) examination, immunohistochemistry (IHC) and direct immunofluorescence (DIF) analyses were performed. Results: The H&E biopsy demonstrated a subepidermal blister, with partial re-epithelialization of the blister floor. Within the blister lumen numerous neutrophils and eosinophils, and occasional lymphocytes were observed. Within the dermis, dilated superficial blood vessels with a mild, perivascular infiltrate of lymphocytes, histiocytes and eosinophils were seen; mild perivascular leukocytoclastic debris was also noted. A periodic acid Schiff (PAS) special stain demonstrated positive staining along the BMZ, and around selected dermal blood vessels and sweat glands. DIF revealed linear deposits of IgG, Complement/C3 and fibrinogen at the BMZ, and around selected dermal blood vessels and sweat glands. By IHC, positive staining for CD8 and CD45, and occasional CD4 positivity was seen on dermal lymphocytes. These lymphocytes were present surrounding selected dermal blood vessels and eccrine sweat glands. Conclusions: The patient displayed immunoreactivity to the BMZ, and also to dermal blood vessels and eccrine glands in his immune response. Similar immune responses would be of interest in immunologic studies of BP patients.